Soil and water management for rice production in Nigeria - Olaleye, A. O.; Osiname, O. A.; Cofie, Olufunke O. (2004)
Rice (Oryza sativa L.) is a unique crop grown in virtually all agro-ecological zones in Nigeria. Much emphasis has been placed on the chemical properties of soils on which rice is grown while there is sparse information on the effect of soil physical properties on grain yield of rice. Field experiments were conducted on upland and wetland soils as they relate to water management for rice production in Nigeria. Results showed that soils with higher clay contents in the top and sub-soils gave higher grain yields of rice compared with soils that are of sandy texture. In terms of agro-climatic characteristics Nigeria could be classified as being highly suitable (S1) for rice cultivation. However, considering the top and subsoil clay contents, these soils are only marginally suitable (S3) for rice production. Soil texture, soil surface relief, groundwater level, as well as number of days of submergence significantly affected the growth and grain yield of rice on lowland soils while clay contents in the subsoil is a significant factor in water retention for upland rice cultivars. These factors must be given proper attention in managing water for rice production in Nigeria.